Probiotic Administration in Infants With Gastroschisis: A Pilot Randomized Placebo-Controlled Trial. Issue 6 (June 2016) - Powell, Weston T.; Borghese, Robyn A.; Kalanetra, Karen M.; Mirmiran, Majid; Mills, David A.; Underwood, Mark A.
ABSTRACT: Objectives: Infants with gastroschisis often require long periods of gastric suctioning and hospitalization. The impact of these interventions on the intestinal microbiota and attempts to alter the microbial community have not been studied. We sought to determine how the intestinal microbiota is influenced by the current treatment of gastroschisis and whether alteration of the intestinal microbiota with a probiotic microbe will influence length of hospitalization. Methods: We performed a randomized, placebo-controlled pilot study of administration of probiotic Bifidobacterium longum subsp. infantis in 24 infants with gastroschisis. The primary outcome was changes in the fecal microbiota, and the secondary outcome was length of hospital stay. Results: Administration of the probiotic or placebo was well tolerated, even during the period of gastric suctioning. The overall microbial communities were not significantly different between groups, although analysis of the final specimens by family demonstrated higher Bifidobacteriaceae, lower Clostridiaceae, and trends toward lower Enterobacteriaceae, Enterococcaceae, Staphylococcaceae, and Streptococcaceae in the probiotic group. Clinical outcomes, including length of hospital stay, did not differ between groups. Conclusions: In this pilot study, there was significant in infants with gastroschisis that was partially attenuated by the administration of B longum subsp. infantis. Abstract : Supplemental Digital Content is available in the text